BLOG: Probabilistic Models with Unknown Objects - Milch, Brian; Marthi, Bhaskara; Russell, Stuart; Sontag, David; Ong, Daniel L.; Kolobov, Andrey (IJCAI 2005, 2005)
This paper introduces and illustrates BLOG, a formal language for defining probability models over worlds with unknown objects and identity uncertainty. BLOG unifies and extends several existing approaches. Subject to certain acyclicity constraints, every BLOG model specifies a unique probability distribution over first-order model structures that can contain varying and unbounded numbers of objects. Furthermore, complete inference algorithms exist for a large fragment of the language. We also introduce a probabilistic form of Skolemization for handling evidence.